Leveraging Technopreneurship and Office and Information Management Programme for Sustainable Development in The Digital Economy - Munirat Opeyemi Adeyeye (The Eastasouth Journal of Social Science and Humanities, 2026)
This paper explores the extent to which technopreneurship with office and information management (OIM) practices can inclusively enhance economic growth and social responsibility. There is a mutual relationship between digital development and entrepreneurship, which, if utilized, can spur a nation into high level of prosperity. Combining information management, technology and entrepreneur with office management will heighten the level of productivity and innovation from employees, hence enabling organizations to contribute their quota to sustainable national development. This paper recognizes the critical need for integrating technopreneurship into office and information management programme in the economic landscape in order to enhance national development. It dives into the concept of technopreneurship in context of digital economy, role of technopreneurship in driving innovation in digital economy, technologies used in office and information management, and challenges and prospects of leveraging technopreneurial culture for sustainability. By utilizing new technologies with efficient information management put in place and imbibing technopreneurial culture, organizations will be able to contribute immensely to sustainable national development. The paper recommends among others that: Government intervention should be comprehensively analyzed and carefully designed to focus on developing technologies; The management of institutions should equip the laboratories and make them to be accessible to students for constant practice on technological tools to acquire the required skills for both technopreneurship and digital economy; Individual office and information management students must be prepared for ongoing learning and upskilling that can enhance self reliance after graduation from school.